Improvement Of Reading Skills Using A Reading Process Approach in Class IV SDN 37 Koto Pulai - Muspita Darefni (Universitas Sebelas Maret, 2020)
The purpose of this study was to describe the improvement of reading comprehension skills by using. This study uses a qualitative and quantitative approach with the type of classroom action research. The results of the research assessment cycle I showed that the achievement obtained by students at the pre-reading stage was 66.2, at the reading stage 65, and at the post-reading stage 60, the percentage of student learning outcomes in the first cycle was 69.7%. In the second cycle, the achievement obtained by the students at the pre-reading stage was 86.5, at the reading stage 90, and at the post-reading stage 79, the percentage of student learning outcomes in the second cycle was 85. Reading comprehension skills could increase with a percentage increase of 15.3%, because in the process of learning to read using the pre-reading, while-reading, and post-reading stages, it can be concluded that classroom action research through the reading process approach can improve students' reading comprehension skills.